Perception of Malaysians at Klang Valley towards halal food products / Nadzirah Abd Wahab - Abd Wahab, Nadzirah (Faculty of Business and Management, 2007)
Halal food is a basic need to every Muslim. It is a universal food requirement, well accepted not only by Muslims but also non-Muslims. Due to greater awareness among Muslims on their responsibility to consume only halal food, the demand for halal food is on the rise. The average halal consumer will also purchase additional groceries and supplies from stores carrying halal products. They want more choices, and are more loyal to stores and halal brands than the average non-halal consumers. This is due to religious affiliation of the products they purchase. The main objective of this paper is to see the perception of Malaysians at Klang Valley and to determine which factors of perceptions might be the most influencing the respondents at that area towards halal food products. The study utilizes the questionnaire as the instrument for collecting data. Validity and reliability test are conducted to ensure the instrument used is reliable. A total of 100 respondents returned their completed questionnaires to be analyzed. From this sample, the respondents included Muslims and non-Muslims. As a whole, the respondents range from 20 years of age to more than 50 years of age and come from a different background. A factor analysis was done for the purpose of determining the construct validity of the questionnaire and seven (7) items were grouped in the perception towards halal food products. The findings give a better understanding of Malaysian's towards halal food. Thus, with a positive reaction from the respondents, Malaysia is ready to market widely more halal food internationally.